2022
DOI: 10.3390/ijerph191912514
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Physical Activity at School on Body Fat Content in School-Aged Children

Abstract: (1) Background: Excessive amounts of adipose tissue is a health risk. The aim of this study was to assess the impact of increased physical activity (PA) at school on body fat content in children aged 10 to 12 years over a 2-year follow-up. (2) Methods: Children born in 2007 (n = 245) in two groups, (1) standard PA and (2) increased PA at school, 4 and 10 h of physical education lessons per week, respectively. BIA measurements of body fat content were taken twice a year. Results were interpreted based on childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…In this study, there were differences in the PA level (PAQ-C), cardiorespiratory endurance (6MWT) and QoL (PedsQL 2.0) between the groups classified by BMI percentile. Studies have been conducted to examine the PA levels, cardiorespiratory endurance and QoL among children with PD, and it has been reported that the majority of them who regularly participated in PA reduced their risk of being overweight and obese, which consequently improved their cardiorespiratory endurance and QoL [ 36 , 37 , 38 ]. Children who were underweight had the lowest scores on the PAQ-C, 6MWT, total PedsQL 2.0 and all sub-dimensions of the PedsQL 2.0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, there were differences in the PA level (PAQ-C), cardiorespiratory endurance (6MWT) and QoL (PedsQL 2.0) between the groups classified by BMI percentile. Studies have been conducted to examine the PA levels, cardiorespiratory endurance and QoL among children with PD, and it has been reported that the majority of them who regularly participated in PA reduced their risk of being overweight and obese, which consequently improved their cardiorespiratory endurance and QoL [ 36 , 37 , 38 ]. Children who were underweight had the lowest scores on the PAQ-C, 6MWT, total PedsQL 2.0 and all sub-dimensions of the PedsQL 2.0.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, children with a healthy weight had the highest score on the PAQ-C, 6MWT, total PedsQL 2.0 and all the sub-dimensions of the PedsQL 2.0. Increasing PA among children with PD reduces the BMI and body mass fat while increasing muscle mass [ 36 ]. Overweight and obese children have lower levels of PA compared to their non-overweight and non-obese peers.…”
Section: Discussionmentioning
confidence: 99%
“…The procedures of anthropometric measurements and the interpretation of the results were described in our previous papers [12,13,42].…”
Section: Measurements 241 Anthropometric Measurementsmentioning
confidence: 99%
“…The study was conducted between 10 and 11 a.m. in the gym with a PE teacher following the guidelines described below [31,32,36]. At the beginning anthropometric measurements were carried out according to the methodology described in previous papers [10,12,13,42].…”
Section: Eurofit Testsmentioning
confidence: 99%